Disseminated Herpes Zoster During COVID-19. Issue 2 (March 2021) - Voisin, Olivier; Deluca, Nina; Mahé, Annabelle; Lelorc'h, Erwan; Hubert, Sidonie; Ménage, Elodie; Borie, Marie-Françoise; Azria, Philippe; Fite, Charlotte; Pilmis, Benoit; Mourad, Jean-Jacques
Abstract : Abstract: During the SARS-CoV-2 pandemic, a variety of dermatological conditions were reported by physicians. Given the context, these lesions have been labeled as secondary to SARS-CoV-2 infection. We report the case of a recurrence of herpes zoster in a patient hospitalized with an SARS-CoV-2 infection. The rash occurred on the 15th day of hospitalization while the patient was recovering from a severe form. Local swab showed the presence of varicella-zoster virus within the vesicles. Dermatological symptoms secondary to COVID-19 have been frequently described. This is the first case that demonstrates the recurrence of herpes zoster during a SARS-CoV-2 infection.